2005
DOI: 10.1007/s00125-005-1916-y
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and glucodynamic variability: assessment of insulin glargine, NPH insulin and insulin ultralente in healthy volunteers using a euglycaemic clamp technique

Abstract: Aims/hypothesis: This single-dose, doubleblind, randomised, parallel-group study evaluated the reproducibility in systemic exposure and glucodynamic effect of insulin glargine, NPH insulin (NPH) and insulin ultralente (ultralente) using the manually adjusted euglycaemic clamp technique. Methods: In total, 36 healthy volunteers received two consecutive s.c. injections (0.4 IU/kg) of glargine, NPH or ultralente with a wash-out period of 7 days between treatments. Results: In healthy volunteers, glargine presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
83
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(90 citation statements)
references
References 19 publications
5
83
1
1
Order By: Relevance
“…Few studies have determined the PD intrasubject variability of glargine (1,11,12), and only one study has made this determination using subjects with T1DM (1). Similar to the results seen in this study, Heise et al (1) found high G tot and R max intrasubject variabilities for glargine.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have determined the PD intrasubject variability of glargine (1,11,12), and only one study has made this determination using subjects with T1DM (1). Similar to the results seen in this study, Heise et al (1) found high G tot and R max intrasubject variabilities for glargine.…”
Section: Discussionmentioning
confidence: 99%
“…1 Pharmacodynamic profile of insulin glargine, reproduced from Scholtz et al (Fig. 1a) [1]. The two lines denote the median GIR after subcutaneous injection of insulin glargine in twelve healthy volunteers, clamped at two different occasions J. H. DeVries (*)…”
mentioning
confidence: 99%
“…To the Editor: Scholz et al present a comprehensive clamp study on pharmacokinetics, pharmacodynamics and variability of insulins NPH, ultralente and glargine [1]. Figure 1a from their article ( Fig.…”
mentioning
confidence: 99%
“…This may again lead to overestimation of the duration of action of the study insulin (D. K. W. Soon, Exploratory and Program Medicine, Lilly-NUS Centre for Clinical Pharmacology, Singapore, personal communication). Moreover, suppression of endogenous insulin secretion is incomplete, with reported reductions in C-peptide levels to about 45% of the baseline values [16] or '>50%' [8]. However, clamp studies in healthy volunteers may serve regulatory requirements (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…For example, insulin glargine's time-action profile has been characterised as being flat [7,8] and as waxing and waning with a maximum effect approximately 10 h after injection [9][10][11]. Also, in one head-to-head study in type 2 diabetic patients the two long-acting insulin analogues were found to be comparable [10], whereas another comparison in individuals with type 1 diabetes showed lower total activity and a shorter duration of action for insulin detemir [12].…”
Section: Conflicting Clamp Datamentioning
confidence: 99%